Targeting Focal Adhesion Assembly by Ethoxyfagaronine Prevents Lymphoblastic Cell Adhesion to Fibronectin. (2012) - Ouchani, F.; Devy, J.; Rusciani, A.; Helesbeux, J. J.; Salesse, S.; Letinois, I.; Gras-Billart, D.; Duca, L.; Duval, O.; Martiny, L.; Charpentier, E.
Abstract : Background : Leukemic cell adhesion to proteins of the bone marrow microenvironment provides signals which control morphology, motility and cell survival. We described herein the ability of ethoxyfagaronine (etxfag), a soluble synthetic derivative of fagaronine, to prevent leukemic cell adhesion to fibronectin peptide (FN/V). Methods : Phosphorylation of fak and pyk2 were evaluated by immunoblotting. Labelled proteins were localized by confocal microscopy. PI 3-kinase activity was evaluated by in vitro kinase assay. Results : Subtoxic concentration of etxfag reduced L1210 cell adhesion to FN/V dependently of β1 integrin engagement. Etxfag impaired FN-dependent formation of β1 clustering without modifying β1 expression at the cell membrane. This was accompanied by a decrease of focal adhesion number, a diminution of fak and pyk2 phosphorylation at Tyr-576, Tyr-861 and Tyr-579, respectively leading to their dissociations from β1 integrin and inhibition of PI 3-kinase activity. Etxfag also induced a cell retraction accompanied by a redistribution of phosphorylated fak and pyk2 in the perinuclear region and lipid raft relocalization. Conclusion : Through its anti-adhesive potential, etxfag, combined with conventional cytotoxic drugs could be potentially designed as a new anti-leukemic drug.